PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Haryati, Retno; Cahyati, Ari Dewi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
The purpose of this study was to determine the presence or absence of earnings management practices and real earnings management accrual on companies listed in the Jakarta Islamic Index (JII) and the effect of GoodCorporate Governance (Board of Independent Commissioners, Institutional Ownership, and the Audit Committee) toEarnings Management (Management profit) substantive or accrual.. The population is all companies listed in theJakarta Islamic Index (JII) during 2010-2013. The sampling technique used purposive sampling. Obtained 32samples of 8 companies. Data analysis methods used logistic regression analysis to real earnings management proxyand multiple linear regression analysis to accrual earnings management proxy. The results showed during the years2010-2014 there were 10 companies that do the real earnings management and all do accrual earningsmanagement. Independent board has significant negative effect on riil earnings management, but it does not affectaccrual earnings management, Institutional Ownership does not affect the riiland accrual earning management, andthe audit committee has significant positive effect on accrual earnings management, but does not affect the riilearning management. The next study is expected to add an independent variable, because there is the possibility ofother factors not included in this study affect the income smoothing and adding the study period.